Predictors of survival outcomes in phase 1 relapsed or refractory multiple myeloma patients. Issue 6 (6th November 2014) - Barbee, Meagan S.; Nooka, Ajay; Kaufman, Jonathan L.; Kim, Sungjin; Chen, Zhengjia; Heffner, Leonard T.; Lonial, Sagar; Harvey, R. Donald
<x xml:space="preserve">Abstract</x> BACKGROUND The categories of the International Myeloma Working Group (IMWG) response criteria for multiple myeloma are based on the magnitude of the change in paraprotein and the normalization of the free light chain ratio (rFLC). However, the relationship between the response by these biomarkers and clinical outcomes has not been validated with novel compounds in the phase 1 setting. Early response predictors may have prognostic value and speed development plans for new agents. METHODS The relationship between biomarkers of response and clinical outcomes was examined in 87 relapsed or refractory multiple myeloma patients enrolled in nontransplant phase I clinical trials from January 2004 through November 2011 at 4 time landmarks. Progression‐free survival (PFS) was the primary outcome, and overall survival (OS) was also assessed. RESULTS The normalization of rFLC within 4 months predicted improvement in PFS (11.3 vs 2.8 months, P = .038), whereas the normalization of rFLC within 12 months predicted improvement in PFS (6.1 vs 2.8 months, P = .015) and OS (45 vs 17.4 months, P = .002). The magnitude of response in paraprotein predicted and correlated linearly with PFS at all time landmarks (R2 = 0.703‐0.943) when it was assessed with 2 different boundaries. CONCLUSIONS These findings suggest that the normalization of rFLC and the magnitude of response are viable biomarkers for surrogate endpoints in early‐phase clinical trials, validate the use of current IMWG response criteria in the phase 1 setting, and support the use of these biomarkers for drug development endpoints. Cancer 2015;121:853–862. © 2014 American Cancer Society.